Timing of Eocene compressional plate failure during subduction initiation, northern Zealandia, southwestern Pacific. Issue 3 (28th January 2022) - Stratford, W R; Sutherland, R; Dickens, G R; Blum, P; Collot, J; Gurnis, M; Saito, S; Bordenave, A; Etienne, S J G; Agnini, C; Alegret, L; Asatryan, G; et al.
SUMMARY: Rapid onset of subduction tectonics across the western Pacific convergent margins in the early Eocene was followed by a slower phase of margin growth of the proto Tonga-Kermadec subduction system north of Zealandia during a middle Eocene phase of tectonic adjustment. We present new age constraints from International Ocean Discovery Program Expedition 371 borehole data on deformation events in northern Zealandian sediments that document the formation of the convergent margin boundary northwest of New Zealand. The deformation shows a shortening event that lasted up to 20 myr and acted over distances of ∼1000 km inboard of the evolving plate margin, just northwest of New Zealand. Multichannel seismic profiles tied to our new borehole sites show shortening occurred predominantly between 45 and 35 Ma with some deformation related to slope failure continuing into the Oligocene. The termination of shortening is linked to opening of the backarc basins of the southwest Pacific and the migration of the Tonga-Kermadec Trench to the east which may have removed the structural evidence of the Eocene plate margin. Palaeogene deformation observed inboard of the evolving proto Tonga-Kermadec subduction system indicates that the lithosphere of northern Zealandia, a region of thin continental crust, was strong enough to act as a stress guide. Compressive stresses that caused intraplate folding and faulting developed behind the initiating subduction system with the finite period of deformation indicating the time frame over which an active convergent margin lay along the northern margin of Zealandia.